Epigenetics: What it is about? - Saade, E.; Ogryzko, V.V. (Вiopolymers and Cell, 2014)
Epigenetics has captured the attention of scientists in the past decades, yet its scope has been continuously changing. In this paper, we give an overview on how and why its definition has evolved and suggest several clarification on the concepts used in this field. Waddington coined the term in 1942 to describe genes interaction with each other and with their environment and insisted on dissociating these events from development. Then, Holliday and others argued that epigenetic phenomena are characterized by their heritability. However, differentiated cells can maintain their phenotypes for decades without undergoing division, which points out the limitation of the «heritability» criterion for a particular phenomenon to qualify as epigenetic. «Epigenetic stability» encompasses traits preservation in both dividing and non dividing cells. Likewise, the use of the term «epigenetic regulation» has been misleading as it overlaps with «regulation of gene expression», whereas «epigenetic information» clearly distinguishes epigenetic from genetic phenomena. Consequently, how could epigenetic information be transmitted and perpetuated? The term «epigenetic templating» has been proposed to refer to a general mechanism of perpetuation of epigenetic information that is based on the preferential activity of enzymes that deposit a particular epigenetic mark on macromolecular complexes already containing the same mark. Another issue that we address is the role of epigenetic information. Not only it is important in allowing alternative interpretations of genetic information, but it appears to be important in protecting the genome, as can be illustrated by bacterial endonucleases that targets non methylated DNA – i. e. foreign DNA – and not the endogenous methylated DNA.